PWE-094 The Prevalence of Anaemia in Inflammatory Bowel Disease in Relation to Disease Activity, as Stratified by Faecal Calprotectin. (4th June 2013) - Muscat, M; Kennedy, N A; Chang, J; Satsangi, J; Arnott, I D; Kingstone, K; Lees, C W
Abstract : Introduction: The prevalence of anaemia in IBD varies significantly between published studies, ranging from 6–74%. However, underlying disease activity, a potential explanation for this variability, has not been accurately correlated with the frequency of anaemia to date. Faecal calprotectin (FC) is a surrogate marker of underlying mucosal inflammation. The objective of this study was to investigate the prevalence of anaemia and its correlation with disease activity in IBD, in a large cohort of patients with matched full blood count (FBC) and FC data. Methods: Patients with confirmed IBD from the Edinburgh faecal calprotectin registry (EFCR) were identified. Where multiple FCs were available, the most recent result was taken as reference. Blood test results were obtained from the electronic record covering a period one month either side of the FC. The WHO criteria was used to define anaemia (Hb < 130 g/L in men, < 120 g/L in women). A FC value of ≥200 µg/g was used to indicate active disease. The cohort was subdivided into 4 groups: active and inactive Crohn's disease (CD), active and inactive Ulcerative colitis (UC). Results: 1226 patients (771 CD, F = 65%, 455 UC, F = 35%) with matched FC and FBC data were analysed. The median age was 44y (IQR 31–57), median disease duration 102 months (IQR 31–207). Overall, 314/1226 patients (25.6%) were anaemic, 185/314 (58.9%) of which were female. Anaemia was observed more frequently in patients with active as opposed to inactive CD (110/328 [33.5%] vs 65/443 [14.7%], p < 0.0001). This pattern was also seen in patients with UC (129/293 [44%] vs 23/162 [14.2%], p < 0.0001). The prevalence of anaemia in active UC was greater than in active CD (p = 0.014); however, this could be explained by the higher median FC in the UC cohort (900 vs. 618, p < 0.0001). There was no statistically significant difference in age or Montreal location (L1 + L3 vs L2, p = 0.16) between the groups. ROC analysis of FC as a predictor of anaemia showed an AUC of 0.69 with a sensitivity and specificity of 0.73 and 0.57 respectively at a cut off of 200 µg/g. Conclusion: In this cohort over 25% of patients with IBD were anaemic. There is a clear correlation between disease activity and anaemia in both CD and UC, but this is unrelated to disease distribution in CD. Anaemia in asymptomatic patients should alert clinicians to the possibility of subclinical active mucosal inflammation. These data and the ROC analysis provide further support for optimising disease treatment in IBD, targeting a FC level of < 200 µg/g. Disclosure of Interest: None Declared.